Pemikiran dakwah Syed Qutb berdasarkan Tafsir Fi Zilal Al-Quran / Halipah Hamzah - Hamzah, Halipah (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2012)
Sayyid Qutb was a prominent figure who had contributed widely in various fields. One of his contributions that can be emulated by Muslims is his insights in his preaching. His struggles in preaching were carried out as a group through collective participation in the movement of the Muslim Brotherhood as well as individually through the writing of books and articles. One of his famous books was according to the interpretations of the Quran Fi Zilal. This study aims to explore the thinking of Sayyid Qutb’s missionary method of analysis based on interpretations of the Quran Fi Zilal. The study has proven that the method based on his missionary thoughts coincides with those outlined in the Quran that use the al-hikmah, al-maw`izah al-hasanah and al-mujadalah methods. Throughout the life of Sayyid Qutb, he was a missionary who was patient, persistent, humble, calm, quiet and always trusting in God.